Nanosponges for Drug Delivery and Cancer Therapy: Recent Advances - Iravani, Siavash; Varma, Rajender S (Nanomaterials (Basel, Switzerland), 2022)
Nanosponges with three-dimensional (3D) porous structures, narrow size distribution, and high entrapment efficiency are widely engineered for cancer therapy and drug delivery purposes. They protect the molecular agents from degradation and help to improve the solubility of lipophilic therapeutic agents/drugs with targeted delivery options in addition to being magnetized to attain suitable magnetic features. Nanosponge-based delivery systems have been applied for cancer therapy with high specificity, biocompatibility, degradability, and prolonged release behavior. In this context, the drug loading within nanosponges is influenced by the crystallization degree. Notably, 3D printing technologies can be applied for the development of novel nanosponge-based systems for biomedical applications. The impacts of polymers, cross-linkers, type of drugs, temperature, loading and mechanism of drug release, fabrication methods, and substitution degree ought to be analytically evaluated. Eco-friendly techniques for the manufacturing of nanosponges still need to be uncovered in addition to the existing methods, such as solvent techniques, ultrasound-assisted preparation, melting strategies, and emulsion solvent diffusion methods. Herein, the recent advancements associated with the drug delivery and cancer therapy potential of nanosponges (chiefly, cyclodextrin-based, DNAzyme, and ethylcellulose nanosponges) are deliberated, focusing on the important challenges and future perspectives.
Keywords: cancer therapy; drug delivery; cyclodextrin-based nanosponges; nanosponges; ethylcellulose nanosponges; DNAzyme nanosponges